Inhibitory effects of sulphated flavonoids isolated from Flaveria bidentis on platelet aggregation - Guglielmone, Hugo (2005)
Flaveria bidentis is a plant species that has as major constituents sulphated flavonoids in the highest degree of sulphatation. Among them, quercetin 3,7,3′,4′-tetrasulphate (QTS) and quercetin 3-acetyl-7,3′,4′-trisulphate (ATS) are the most important constituents. Both showed anticoagulant properties. The objective of the present study was to evaluate the effects of these flavonoids on human platelet aggregation in comparison with the well-known inhibitor quercetin (Qc) by using several agonists. Platelet-rich plasma (PRP) or washed human platelets (WP) were incubated with different concentrations of the flavonoids to be tested (1 to 1000 μM, final concentration), and the platelet aggregation was induced by using adenosine 5′-diphosphate (ADP), epinephrine (EP), collagen, arachidonic acid (AA) and ristocetin as agonists. QTS (500 μM) and Qc (250 μM) markedly inhibited platelet aggregation with all the aggregant agents, except ristocetin, whereas ATS (1000 μM) showed only slight antiplatelet effects. In addition, QTS and Qc antagonized the aggregation of PRP or WP induced by U-46619, a mimetic thromboxane A2 (TxA2) receptor agonist. Challenged with collagen or arachidonic acid, the thromboxane B2 (TxB2) formation was also inhibited by the flavonoids, mainly by QTS and Qc, in WP. These results demonstrate that QTS and in minor extension ATS induce a deleterious effect on the production of TxA2, as judged by TxB2 formation, in stimulated WP and a marked interference on the TxA2 receptor according to the profile of inhibition of the agonist-induced platelet aggregation when using ADP, EP, AA and collagen and confirmed with U-46619.